PENGARUH BUDAYA ORGANISASI, STRES KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Sudha Cahyana, I Gede; Jati, I Ketut (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
The more complex the business world and the growing demand for transparency and accountability demands optimal performance of employees. Employee performance based on previous research showing that performance is influenced by several factors. This study aims to investigate the influence of organizational culture, job stress and job satisfaction to employee performance. This research was conducted on the Tax Office Primary in East Denpasar in 2016. The samples used 70 employees to participate in this study. The sample in this study was determined by single random sampling method. Data were collected using a survey method. Data analysis technique used is multiple linear regression. Based on the results of multiple regression analysis with significance level of 5 percent, then the results of this study show that organizational culture have positive influence on employee performance, variable job stress have positive effect on employee performance, job satisfaction have positive effect on employee performance.
Keywords: organizational culture, job stress, job satisfaction, employee performance